Non-fullerene OSC: The effects of active and electron transport layers' thickness towards 19.5% efficiency - Burak Yahya Kadem; R.K. Fakher Alfahed (Revue des Énergies Renouvelables, 2025)
The effects of the active layer thickness of the organic solar cells based on PM6, D18 and L8-BO materials as well as the effects of electron transport layer thickness are examined using Organic and hybrid Material Nano Simulation (Oghma) software. Several active layer thicknesses are used starting 50nm to 300nm to choose the optimum active layer thickness. For PM6:L8-BO blend, the optimum active layer thickness of is found to be 90nm with a PCE of 13.52%. Whereas, the optimum active layer thickness of D18:L8-BO blend is demonstrated almost similar characteristics with PCE of 13.2% for an optimum active layer thickness of 90nm. Using ternary blend PM6:D18:L8-BO active layer enhances the PCE to 17.5% when the optimum active layer thickness is 80nm. Also, the use of different electron transport layer thickness has resulted in further increase in the PCE to reach as high as 19.5% with the thickness of 20nm.